Hubungan Dukungan Keluarga dengan Tingkat Kecemasan Pasien Pre Operasi di Ruang Rawat Inap Bedah RSD Gunung Jati Kota Cirebon - Sopi Cahyani; Bayu Nirwana; Habsyah Saparidah Agustina (Jurnal Ventilator, 2024)
Surgery is a way of making incisions in the patient's body. Symptoms that appear before surgery are anxiety. To reduce feelings of anxiety, family support is needed. The support provided by the family can provide feelings of joy, security and comfort. The aim of this study was to determine the relationship between family support and anxiety levels in pre-operative patients in the Surgical Inpatient Room at RSD Gunung Jati Cirebon. This research is a type of quantitative research. The sampling technique used was purposive sampling with a total sample of 69 patients. Data were collected using family support questionnaires and anxiety levels, data analysis used the Spearman rank test. The research results showed that almost all respondents had high family support with 58 patients 84.1%, and most respondents had mild levels of anxiety, 49 patients 71,0%. The Spearman rank test obtained a p-value of 0.000, which means the hypothesis was accepted. From this research, it can be concluded that there is a relationship between family support and the level of anxiety in pre-operative patients in the surgical inpatient room at Gunung Jati Hospital, Cirebon City. The results of this research can be used as input before taking action requiring family support to reduce the patient's preoperative anxiety level.